Analysis of body composition in treatment people with mental disorders - Sidney Ferreira Farias; Edio Luiz Petroski; Maika Arno Roeder (Universidade Federal de Santa Catarina, 2001)
Drug-based intervention is used in the treatment of mental disorders with the objective of ameliorating symptoms, acting through the central nervous system. Mood stabilizers and antidepressants have side effects relating to excess weight gain. Faced with this fi nding, objective of this study is to assess the body composition of people on this class of drugs. The study population consisted of individuals on treatment, 10 men and 10 women, intentionally selected by psychotropic drug use for at least 6 months. Quantity and distribution of fat was determined using BMI, the waist/hip ratio, the body fat percentage according to anthropometric methods and by bioimpedance. Data related to calorie intake and the practice of physical activity were obtained from the treatment team. Data were represented with descriptive statistics in mean, minimum and maximum values with standard deviations, the t test to detect differences between groups, and one-way ANOVA to compare equations. The signifi cance level adopted was p<0.05. The results indicate a clear relationship between alterations in morphological composition and excessive body fat and the topography of adipose tissues in individuals that take antidepressants and mood stabilizers. RESUMO A intervenção medicamentosa é utilizada no tratamento dos transtornos mentais e tem por objetivo, combater os sintomas da doença, atuando no sistema nervoso central. Os estabilizadores do humor e antidepressivos apresentam efeitos colaterais relacionados ao sobrepeso. Diante desta constatação este estudo teve por objetivo, avaliar a composição corporal de pessoas que fazem uso destes grupos de medicamentos. A população deste estudo, constituiu-se de indivíduos em tratamento, sendo a amostra de 10 homens e 10 mulheres, selecionados intencionalmente, por utilizarem estes psicofármacos pelo menos há 6 meses. Na determinação das variáveis quantidade e distribuição de gordura utilizou-se o IMC, relação cintura/quadril, e percentual de gordura através de medidas antropométricas e de impedância bioelétrica. Dados relativos à ingestão calórica e à prática da atividade física foram coletados com a equipe terapêutica. Adotou-se a análise descritiva dos dados, sendo apresentados os valores médios, mínimos e máximos, desvio padrão e o test t para determinar as diferenças entre os grupos masculino e feminino; e análise de variância (ANOVA One-Way), para diferenças entre as equações. O nível de signifi cância adotado foi de p<0,05. Os resultados indicam que existe nítida relação entre alterações do componente morfológico com excesso de gordura corporal e com a topografi a do tecido adiposo em indivíduos que fazem uso de antidepressivos e estabilizadores do humor.